The Laboratory Diagnosis of Hepatitis B Virus - Mel Krajden; Gail McNabb; Martin Petric (Canadian Journal of Infectious Diseases and Medical Microbiology)
Hepatitis B virus (HBV) chronically infects approximately 250,000 Canadians and 350 million people worldwide. Without intervention, approximately 15% to 40% of chronically infected individuals will eventually develop cirrhosis, end-stage liver disease or hepatocellular carcinoma, or require liver transplantation. The availability and extensive use of the HBV vaccine has dramatically reduced the number of incident infections in Canada and worldwide. Effective therapeutic agents have been and continue to be developed to treat chronic infection. The present review provides a comprehensive overview of diagnostic tests for HBV infection and immunity, and elaborates on HBV risk factors, vaccine prevention and therapeutic monitoring. HBV diagnosis is accomplished by testing for a series of serological markers of HBV and by additional testing to exclude alternative etiological agents such as hepatitis A and C viruses. Serological tests are used to distinguish acute, self-limited infections from chronic HBV infections and to monitor vaccine-induced immunity. Nucleic acid testing for HBV-DNA is increasingly being used to quantify HBV viral load and measure the effectiveness of therapeutic agents. Given the multitude of available tests and the complexity of clinical management, there is a critical need for greater coordination among clinicians, diagnostic laboratory personnel and researchers to define optimal laboratory diagnostic and monitoring assays so that the appropriate tests are used to maximize prevention and optimize treatment outcomes.